Comparison of panoramic radiography with cone beam computed tomography for assessing the relationship between posterior teeth and the maxillary sinus - Rojas, Jhonnathan (2023)
Objective: To compare panoramic radiography (PR) with cone beam computed tomography (CBCT) to assess the relationship between posterior teeth and the maxillary sinus. Material and methods: A comprehensive analysis was conducted on 533 posterior teeth of the maxilla of 80 subjects who underwent panoramic and tomographic imaging at the Teaching Dental Center (TDC) of the Universidad Peruana Cayetano Heredia (UPCH) between 2016 and 2019. It was a cross-sectional, observational, descriptive, and retrospective study. Data and observations were recorded on a data sheet designed for this study.Results: The most frequent relationship between teeth and maxillary sinus (MS) was class 0 (root apex without contact with the floor of the MS), predominantly observed on women aged 48 to 57, and in both premolars. In class 0, a greater concordance was found between both radiographic methods. PR was very accurate in detecting class 0 in both premolars, but very inaccurate in detecting class 3 (floor of MS curved downward and apex above it) in all tooth types. Conclusions: Panoramic and tomographic images present low concordance in class 3 relationships as all cases observed in panoramic images show a lower classification in tomography. Therefore, PR is sufficient to provide the true relationship between premolars and maxillary sinus. However, in the case of molars, a three-dimensional image is required.